HOW APPLES PLANNED OBSOLESCENCE CRIME INCREASES INEQUALITY: A RESPOND ON CAPITALISM, JURIDIFICATION, AND SOCIAL CONTROL - Christy, Giovanni; hamid, supardi (Jurnal Ilmu Kepolisian, 2024)
This essay examines the infamous contemporary crime called as planned obsolescence. The ramification of the capitalist system has made prominent mega-tech companies to shape technological standard and influence other to comply and acquire to such condition. It creates a regime of technological hegemonyin this case, I particularly place the utter focus to the Apple Companys alleged attempt to dominate the technology market by perpetrating certain time-window for science and technology inventions, inter alia“the manufacture, software system and design, to be out of date or deemed as obsolete when they have reached certain designated period of time, hence forcing the customers to make repeated purchase to keep up with the latest digital trend as the only way to survive technologically. Further, I will put into scrutiny the phenomenon of planned obsolescence regards to the framework of social crimes and its abominable excess of arbitrary social control that creates inequality to the society, particularly viewed from an overwhelmingly Foucauldian post-structuralist approach, specifically to the loyal technology customers. To present a thorough result of this study, I use a systematic overview of literature reviews by qualitative analysis.